2000
DOI: 10.1002/(sici)1097-0223(200004)20:4<293::aid-pd801>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound findings in affected and unaffected pregnancies that are screen-positive for trisomy 18: the California experience

Abstract: This study investigated whether significant differences in ultrasound findings exist between trisomy 18 affected and unaffected pregnancies positive by serum screening. Ultrasound reports were reviewed for 335 screen-positive women. This represented 65% of all trisomy 18 screen-positive patients who had follow-up services at any of 117 Californian state-approved Prenatal Diagnosis Centers during a six-month period from November 1, 1995 to April 30, 1996. Ultrasound reports were available for 100% of trisomy 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…They are seen in up to half of second-trimester fetuses and are often found with other anomalies. [3][4][5][6][7][8][9][10][11][12][13] In the nearly 2 decades since the initial report by Chudleigh et al, 1 a large volume of literature has been published regarding the sonographic detection of choroid plexus cysts in the second trimester. Despite this, a consensus of opinion has yet to be reached on the genetic significance and appropriate management when these cysts are detected as an isolated finding.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…They are seen in up to half of second-trimester fetuses and are often found with other anomalies. [3][4][5][6][7][8][9][10][11][12][13] In the nearly 2 decades since the initial report by Chudleigh et al, 1 a large volume of literature has been published regarding the sonographic detection of choroid plexus cysts in the second trimester. Despite this, a consensus of opinion has yet to be reached on the genetic significance and appropriate management when these cysts are detected as an isolated finding.…”
contrasting
confidence: 70%
“…Previously published reports detailing the sonographic findings with trisomy 18 show that, although choroid plexus cysts are seen frequently, most are present with other sonographic findings. [5][6][7][8][9][10][11][12][13] In the 223 fetuses from these combined series that had second-trimester sonograms, isolated choroid plexus cysts were not a common finding (6.7%).…”
Section: Discussionmentioning
confidence: 99%
“…13 We found that most fetuses with trisomy 18 had major congenital heart disease (84%) and central nervous system abnormalities (87%) on sonography. Our sensitivity for prenatally detecting major heart disease was much higher than that of most other studies, which reported varying sensitivities, such as 8%, 3 37%, 4 38%, 2 39%, 15 and 67%. 8 This may be attributable to the detail with which each fetal heart is examined sonographically at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 23 fetuses, 65% (n = 15) had abnormal ultrasonographic findings. 22 Congenital heart defects were identified in 39% of fetuses. 22 The authors also reported results from 142 cases of trisomy 18 during a more recent survey (1997 to 1999) and found the ultrasonographic detection rate for trisomy 18 was virtually identical (66%).…”
Section: Discussionmentioning
confidence: 99%